A new look at the architecture and dynamics of the Hydra nerve net - Keramidioti, Athina; Schneid, Sandra; Busse, Christina; Cramer von Laue, Christoph; Bertulat, Bianca; Salvenmoser, Willi; Hess, Martin; Alexandrova, Olga; Glauber, Kristine M; Steele, Robert E; Hobmayer, Bert; Holstein, Thomas W.; et al. (eLife, 2024)
The Hydra nervous system is the paradigm of a ‘simple nerve net’. Nerve cells in Hydra, as in many cnidarian polyps, are organized in a nerve net extending throughout the body column. This nerve net is required for control of spontaneous behavior: elimination of nerve cells leads to polyps that do not move and are incapable of capturing and ingesting prey (Campbell, 1976). We have re-examined the structure of the Hydra nerve net by immunostaining fixed polyps with a novel antibody that stains all nerve cells in Hydra. Confocal imaging shows that there are two distinct nerve nets, one in the ectoderm and one in the endoderm, with the unexpected absence of nerve cells in the endoderm of the tentacles. The nerve nets in the ectoderm and endoderm do not contact each other. High-resolution TEM (transmission electron microscopy) and serial block face SEM (scanning electron microscopy) show that the nerve nets consist of bundles of parallel overlapping neurites. Results from transgenic lines show that neurite bundles include different neural circuits and hence that neurites in bundles require circuit-specific recognition. Nerve cell-specific innexins indicate that gap junctions can provide this specificity. The occurrence of bundles of neurites supports a model for continuous growth and differentiation of the nerve net by lateral addition of new nerve cells to the existing net. This model was confirmed by tracking newly differentiated nerve cells.
Online verfügbar: 22. Februar 2023, Artikelversion: 26. März 2024
Gesehen am 13.08.2024